Parent–offspring brain similarity: Specificities and commonalities among sex combinations–the transmit radiant individuality to offspring study - Izumi Matsudaira; Ryo Yamaguchi; Yasuyuki Taki (iScience, 2025)
Summary: Research suggests that parent–offspring brain similarities may underlie the intergenerational transmission of behavioral traits. However, most studies have focused on mothers and offspring, with few including fathers. This study aimed to extend our understanding of parent–offspring neural similarities by examining parent–offspring trios. The study included 152 Japanese biological trios consisting of adolescents or young adults and their fathers and mothers from the Transmit Radiant Individuality to Offspring (TRIO) study. We analyzed brain structural similarities across different parent–offspring sex combinations. Our findings confirmed that correlations in brain structural features were significantly stronger in parent–offspring dyads than between unrelated individuals. Notably, sons and daughters exhibited brain regions similar to their fathers only, mothers only, both, or neither. These results provide insights into genetic and environmental factors influencing brain development and aging across generations and could contribute to research on mechanisms underlying the intergenerational transmission of various traits.